PWE-177 The functional relevance of toll-like receptor 4 mutations in oesophageal adenocarcinoma. (22nd June 2015) - Fels Elliott, DR; Verstak, B; Li, X; Symmons, MF; Gay, NJ; Fitzgerald, RC
Abstract : Introduction: Altered innate immune signalling may disrupt host-microbe homeostasis and promote an inflammatory microenvironment that favours tumourigenesis. The aim of this project was to assess whether somatic mutations in oesophageal adenocarcinoma (OAC) could interfere with Toll-like receptor (TLR) signalling, with a specific focus on TLR4. Method: We interrogated the mutational profiles of TLR genes in 170 OAC samples, which had undergone whole genome sequencing as part of the oesophageal ICGC study. We performed site-directed mutagenesis and created 13 plasmids expressing mutant TLR4 with a CMV promoter (12 single nucleotide variants (SNVs), and one plasmid combined two SNVs). Luciferase reporter gene assays were performed in HEK293 cells stimulated with synthetic monophosphoryl lipid A (MPLA) to assess how the mutants altered TLR4 signalling and downstream activation of nuclear factor kappa B (NF-κB). Two of the TLR4 mutants were taken forward for transfection into the OAC cell line OE33, and ELISA was used to measure cytokine secretion after stimulation with MPLA. Results: The TLR signalling pathway appeared to be recurrently mutated with missense mutations in 23/170 (13.5%) of tumour samples, including mutations in TLR1 (1.2%), TLR2 (0.6%), TLR4 (4.7%), TLR5 (0.6%), TLR7 (1.8%), TLR9 (1.2%), and MYD88 (1.5%). Based on our data and another recent study by Dulak et al . 1, TLR4 mutations were the most frequent (5.4% combined data). One tumour sample contained two TLR4 mutations, E439G and F703C. Interestingly, the mutation E439G was identified both in our dataset and in the study by Dulak et al . Furthermore, in silico modelling suggested that the E439G mutation disrupts hydrogen bonds in the binding site of LPS and MD2. The use of NF-κB luciferase reporter assays demonstrated a significant decrease in ligand-dependent signalling for 8/12 of the TLR4 mutations tested in HEK293 cells. A double mutation of E439G with F703C revealed a further decrease in TLR4 signalling. Similarly, the concentration of IL-8 was lower for TLR4 mutants E439G and E439G+F703C transfected into OE33 cells stimulated with MPLA, in comparison to wild-type TLR4. Conclusion: TLR4 is recurrently mutated in OAC, and the majority of these mutations showed decreased TLR4 signalling in response to ligand stimulation, both in HEK293 and OE33 cells. The biological relevance of this in relation to host-microbe homeostasis and carcinogenesis is being explored. Disclosure of interest: None Declared. Reference: Dulak AM, et al . Exome and whole-genome sequencing of esophageal adenocarcinoma identifies recurrent driver events and mutational complexity. Nat Genet. 2013;45(5):478–486.